Performance Evaluation of Multiple Ultrasonographical Methods for the Detection of Primary Sjögren’s Syndrome - Xu, Shihao; Luo, Jing; Zhu, Chengwei; Jiang, Jiachun; Cheng, Hui; Wang, Ping; Hong, Jingwei; Fang, Jinxia; Pan, Jingjing; Brown, Matthew A.; Zhu, Xiaochun; Wang, Xiaobing (Frontiers in Immunology, 2021)
Major salivary gland ultrasonography (SGUS) is increasingly being recognized as critical roles in differentiating primary Sjögren’s syndrome (pSS) from other connective tissue disorders. Contrast enhanced ultrasonography (CEUS) has been reported to evaluate micro-vascularity of lesions in different tissues with objective angiographic index, eliminating the observer-dependent defect of ultrasonography. However, there are few relevant studies concentrating on the application of CEUS in the early diagnosis and assessment for pSS and their clinical utility prospect remains uncertain. In this study, a total of 227 eligible patients were enrolled, including 161 pSS and 66 non-pSS patients with comprehensive ultrasonographic evaluation of the parotid and submandibular glands, including greyscale ultrasonography, colour Doppler sonography (CDS), and CEUS. Compared with non-pSS, pSS patients had significantly higher greyscale US scores and CDS blood grades in the parotid gland, and significantly higher greyscale US and CEUS scores in the submandibular glands. Diagnostic model combined ultrasonographic signatures and anti-SSA/Ro60 and keratoconjunctivitis sicca (KCS) tests showed a remarkable discrimination (mean area under curve: 0.963 in submandibular glands and 0.934 in parotid glands) for pSS, and the nomogram provided excellent prediction accuracy and good calibration in individualised prediction of pSS. A combination of multiple ultrasonographical examinations of the major SGs is a promising technique that may be used as a practical alternative to minor salivary gland biopsy in the detection of pSS.